High-resolution taphonomy of the Lower Cretaceous “Amargosa Biota”, Central Tucano Sub-Basin, Bahia, Brazil: Implications for the paleoenvironmental dynamics of a new Konservat-Lagerstätte - Souza, T. G.L. [UNESP]; Matos, S. A. [UNESP]; Varejão, F. G.; Rodrigues, M. G. [UNESP]; Ribeiro, A. C.; Freitas, B. T.; Warren, L. V. [UNESP]; Assine, M. L. [UNESP]; Simões, M. G. [UNESP] (Elsevier, 2022)
We report the Amargosa Biota from the middle part of the Lower Cretaceous Marizal Formation (Central Tucano Sub-Basin, NE Brazil), as a new Konservat-Lagerstätte. Exceptionally preserved fossils are confined to the lower part of an up to 15-m-thick, mud-dominated succession, named Amargosa Bed. Seven bedding planes (L0-L6) with distinct sedimentological and taphonomic attributes were identified in the type section (Amargosa Village, Euclides da Cunha County, Bahia State), distributed in an ~1-m-thick succession of well-laminated claystone, mudstone, siltstone, and very fine-grained sandstone. These contain ostracods, spinicaudatan carapaces, palaemonid shrimps, fish, and comminuted plant remains. Fossils occur in high concentration on at least four bedding planes (i.e., L2, L3, L5, and L6), forming polytypical assemblages that are dominated by one of the fossil groups. Assemblages are formed mainly by autochthonous to parautochthonous elements, representing variable, but limited, temporal mixing. A key attribute of some fossil-rich strata (L3, L5, and L6) is the preservation of poorly biomineralized organisms and/or of complete soft-bodied parts, which are typically prone to destruction due to rapid decay or bioturbation. The polytypical nature of these fossil assemblages, interbedded with non-fossiliferous intervals, suggests mass mortality events, probably caused by abrupt changes in water parameters (anoxia, salinity, pH, among others). The dark greenish gray color (yellowish when weathered), and the finely laminated nature of the claystone, siltstone, and mudstone containing members of the Amargosa Biota indicates that the benthic infaunal life was absent or, at least, very scarce in a locally, relatively deep, oxygen-poor lake bottom. Anoxia and high salinity, linked with local semi-arid conditions during the Lower Cretaceous may have played key roles in the exceptional preservation of some fossils (shrimps, fish). Finally, our data provide a more comprehensive understanding of the temporal distribution of taxa and taphonomic processes associated with the complex genesis of the fossil-bearing interval of the Amargosa Bed in its type locality.
Keywords: Aptian; Exceptional fossilization; Marizal Formation; Paleoenvironment